Machine-Learning-Assisted Intelligent Processing and Optimization of Complex Systems - Luo, Xiong; Yuan, Manman (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains 15 articles from the Special Issue of the MDPI journal Processes on "Machine Learning-Assisted Intelligent Processing and Optimization of Complex Systems". These articles focus on the most recent developments in intelligent optimization methods and their applications in various test cases. The reprint covers various topics, including distributed multiagent modeling, metaheuristic algorithms, multisource data fusion, mobile computing and mobile sensing, machine learning-based intelligent processing for modeling complex manufacturing systems, and data-driven intelligent modeling.Focusing on the abovementioned subjects, this reprint can be useful for researchers interested in intelligent optimization techniques and their applications in the fields of artificial intelligence and machine learning. We believe that this reprint will encourage the convergence between many communities.